Interaction Between Oryctes Rhinoceros and Leaves’ Nutrient Content in Oil Palm - Zaini, Mohd Rasdi; Hazlee, Nurul Farahana Hazira; Karim, Fathul Nabila Abdul (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
A study meant to evaluate the relationship between the presence of Oryctes rhinoceros to the oil palm in relation to the leaves’ nutrient content which is Phosphorus (P) and Potassium (K). Appropriate fertilization is one of the methods that can help to suppress the pests’ presence in the field. In general, insects’ pests are attracted to the plants that are supplied with excess supply of nutrient as it can help them to develop better in future as these nutrient play their roles in aiding through growths and insects’ fecundity. Data on nutrient status were collected were Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Copper (Cu) and Zinc (Zn). These data had been collected twice per month which were at the middle and at the end of each month. Four samples of leaves were taken from four sampling oil palm trees of each treatment. Leaves from ninth or seventeenth fronds were chosen as it is the best most ideal fronds to be used for leaf analysis to identify the nutrient content. The result of this study showed that Phosphorus (P) exerted a strong positive relationship with the presence of Oryctes rhinoceros in the oil palm while Potassium (K) showed a strong negative relationship between the two variables. Thus, developing awareness to the growers to this nutrients-balancing issue would be good for future agriculture in future as it is clear now that balanced nutrition is primordial to ensure availability of nutrients uptake by plants.